Counter-terrorism and the suppression of political pluralism : an examination of the anti-terrorism proclamation of Ethiopia - Kotey, Nii Ashie (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.